UNDERSTANDING FEMALE SEGMENTS BASED ON BENEFIT OF LOYALTY PROGRAM - Sutarso, Yudi; Sekarsari, Larasati Ayu; Ilfitiah, Aniek Maschudah; Martha, Laila Saleh (Universitas Brawijaya, Indonesia, 2023)
loyalty programs in banking need to look at the dynamics of female consumers, especially when digital businesses dominate marketing transactions. In the literature, segmentation studies are mostly carried out on retail services, airlines, and hotels, which are rare in banking, especially related to loyalty program services. Therefore, this study is expected to close the gap without a segmentation study in a banking context. This study aims to identify the female customer segment by assessing the bank's loyalty program and relating it to its perceived convenience, security, and reliability. The study employed the two most prominent banks in Indonesia, with 208 female customers as respondents. The purposive sampling method was used as a method of selecting samples. Data were reduced using factor analysis and categorized using cluster analysis. The main result identifies four factors underlying the benefits of loyalty programs: quality of communication, policy, rewards, and website quality. Three segments of loyalty program female consumers were identified: apathetic (25%), active (31%), and passive segments (44%). In further analysis, three segments of females were analyzed regarding the bank saving account's convenience, reliability, and security. Results confirm that all three segments were unique and distinguished one from another. This study's implication guides managing the types of female customers at the bank, especially loyalty programs.